1993
DOI: 10.1099/00221287-139-11-2841
|View full text |Cite
|
Sign up to set email alerts
|

UV inhibition of the nematode infection process in Arthrobotrys oligospora and Dactylaria candida

Abstract: The effects of UV irradiation on infection of nematodes by two nematode-trapping fungi were studied. Five minutes UV irradiation of the fungi caused an inhibition of the infection process in both Arthrobotrys oligospora and Dactylaria candida. After the nematodes were captured, the infection process stopped; the nematodes were still moving at a time when the nematodes in untreated controls were completely digested. The UV-irradiated fungi were still alive and were capable of further growth. After 15 min UV irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Both explanations are feasible in this context. Early experiments in M. haptotylum showed that treatment with the protein synthesis inhibitor cycloheximide does not affect the infection process (43). Thus, the traps of M. haptotylum appear to contain many of the proteins needed in the early stages of infection, and it is reasonable to assume that trap cells can tightly control the translation and degradation of these proteins to minimize the cost of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both explanations are feasible in this context. Early experiments in M. haptotylum showed that treatment with the protein synthesis inhibitor cycloheximide does not affect the infection process (43). Thus, the traps of M. haptotylum appear to contain many of the proteins needed in the early stages of infection, and it is reasonable to assume that trap cells can tightly control the translation and degradation of these proteins to minimize the cost of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It includes the weather conditions and the edaphic factors. Among all the weather conditions, UV irradiation, as a common cause of spore inactivation in the field, is the most reported factor, e.g., in one study, five-min UV irradiation of the nematophagous fungi Arthrobotrys oligospora and Dactylaria candida caused an inhibition of the infection process (Friman 1993). Besides, the effect of the edaphic factors in which the MCAs are deployed is also important.…”
Section: Environmentmentioning
confidence: 98%
“…The bactericidal action of UVB is well known (12) and ambient UVB in sunlight plays a major role in controlling the growth of baterioplankton in the surface layer of the ocean (13). Ambient UVB also inhibits the infection of nematodes by nematode-trapping fungi (14), and ambient UVB reduces the photosynthesis and growth of benthic (bottomdwelling) diatom communities and inhibits the growth of algal consumers such as larval chironomids (15).…”
Section: Possible Biological Implications Of Sharplyreduceduvbmentioning
confidence: 99%